2021
DOI: 10.1080/23322039.2020.1860282
|View full text |Cite
|
Sign up to set email alerts
|

On the robust drivers of public debt in Africa: Fresh evidence from Bayesian model averaging approach

Abstract: While economic theory suggests a wide range of potential drivers of public debt, there is little consensus regarding the most relevant ones. This paper analyzes the determinants of the public debt in Africa. This is done by adopting a Bayesian Model Averaging (BMA) approach applied to data of 51 African countries, spanning the period 1990-2018. Our results suggest that, among the set of twentyseven (27) regressors considered, those reflecting international financial and institutional conditions as well as inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
3
14
1
Order By: Relevance
“…The result confirmed the crowding-out and debt overhang hypothesis which argued that when government debt accumulation trend borders on financial profligacy, the debilitating effect of servicing such debt constitute a drain of scarce foreign exchange that could have been used for productive investment in infrastructure thereby impeding growth. The result is consistent with the findings of Saxena and Shanker (2018) and Madow et al (2021) who reported a significant negative impact of debt service payment on long-term economic growth in India and African countries, respectively.…”
Section: Long-run Impact Of Public Debt On Economic Growth In Nigeriasupporting
confidence: 92%
See 3 more Smart Citations
“…The result confirmed the crowding-out and debt overhang hypothesis which argued that when government debt accumulation trend borders on financial profligacy, the debilitating effect of servicing such debt constitute a drain of scarce foreign exchange that could have been used for productive investment in infrastructure thereby impeding growth. The result is consistent with the findings of Saxena and Shanker (2018) and Madow et al (2021) who reported a significant negative impact of debt service payment on long-term economic growth in India and African countries, respectively.…”
Section: Long-run Impact Of Public Debt On Economic Growth In Nigeriasupporting
confidence: 92%
“…Capital flight in turn reduces domestic savings and investment, thus reducing growth, the tax base and debt servicing capacity. The diversion of foreign exchange to debt servicing also limits import capacity, competitiveness, and investment and thus growth (Madow et al, 2021).…”
Section: The Debt Overhang Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the determinants of fiscal deficits is important given that persistent deficits quickly lead to the accumulation of public debt, especially in low- and middle-income countries ( World Bank-IMF, 2018 ). Public deficits also influence the level of a country’s public debt ( Bittencourt, 2015 ; Gargouri and Ksantini, 2016 ; Delgado-Téllez and Pérez, 2020 ; Ioannou, 2022 ; Nagou et al., 2021 ). In order to cover its deficit, the government needs to accumulate public debt, having to borrow money from third parties.…”
Section: Literature Reviewmentioning
confidence: 99%